English Language Proficiency of Science and Mathematics Teachers: A Basis for English Enhancement Program - Hernando L. Bernal Jr.; Araceli Mligalig (RIRAI Publisher, 2023)
The study was an attempt to assess the English language proficiency of Mathematics and Science teachers. The respondents of the study were 38 Mathematics teachers and 34 Science teachers from a Higher Education Institution. The data were gathered using self-constructed test as the research instrument. Its validity and reliability using index of discrimination and Spearman Brown Prophecy Formula, respectively. As the study employed the quantitative non-experimental design, analysis and interpretation were made using frequency, percent, mean standard deviation, Pearson product-moment coefficient of correlation r. analysis of variance and t-test. Nearly 2 out 5 Mathematics and Science Teachers were master’s degree holders and almost the same number were baccalaureate degree holders. Both groups of teachers were found to have average level of English language proficiency in reading and writing skills, but below average level in grammar, specifically subject-verb agreement, preposition, and vocabulary. In all these skills, the Mathematics and Science teachers have the same level of proficiency. Among the three skills, those of reading and writing were significantly higher than grammar.Teachers with higher educational attainment, longer teaching experience and have passed licensure examination were those with higher level of English language proficiency in general, and in trichotomized component of reading skills, writing skills, and grammar. As an output of the study, an English enhancement program, focused on grammar was developed which can be accessed on-line.